Isolation and characterization of probiotic Lysinibacillus species from the gastrointestinal tract of large yellow croaker (Larimichthys crocea) - Yao, Yuxin; Wang, Xi; Lin, Xiangyang; Wu, Jianshao; Wang, Pan; Zhu, Chuanzhong; Yan, Qingpi (Frontiers in Marine Science, 2024)
The objective of this study was to identify effective strategies for disease prevention and control that circumvent antimicrobial resistance (AMR) issues, thereby facilitating sustainable aquaculture practices. This research focused on isolating probiotic Bacillus strains from the intestinal tract of healthy large yellow croaker (Larimichthys crocea). Among the 11 strains tested, four demonstrated protease and lipase activities. Further testing identified one strain, Lysinibacillus sp. (LYD11), with strong inhibitory activity against Vibrio harveyi and Vibrio alginolyticus, two major pathogens of the large yellow croaker. The screened strains showed more than 45% co-aggregation with five pathogens and were capable of inhibiting pathogen colonization through competition, repulsion, and substitution adhesion of 20.56 to 48.45%, 40.37 to 75.62% and 55.51 to 85.30%, respectively. The hydrophobicity and self-aggregation rates of LYD11 were 82.73% and 49.47%, respectively, indicating a potent ability for adhesion and colonization within the fish intestine. LYD11 demonstrated robust growth under the NaCl 0.5-3.5% and pH range of 6-8 and was unaffected by the gastrointestinal environment. Safety evaluations at high concentrations in grouper, in both injected and fed groups, indicated no adverse effects, as evidenced by the absence of morbidity or mortality. Consequently, Lysinibacillus sp. LYD11 emerges as a potential probiotic candidate for the prevention and control of bacterial diseases in the large yellow croaker.